Double stent fracture and in‐stent restenosis due to nodular calcification treated with Shockwave coronary intravascular lithotripsy. Issue 4 (16th January 2020) - McCutcheon, Keir; Bennett, Johan; Adriaenssens, Tom
Abstract: We describe the fracture of a double layer of stents caused by nodular calcification. This resulted in recurrent in‐stent restenosis, which was treated with Shockwave coronary intravascular lithotripsy.